From Carpentaria to The Swan Book: finding a voice to narrate and resist the threat of extinction in Alexis Wright’s latest work - Anne LE GUELLEC-MINEL (E-REA)
Alexis Wright is an acclaimed Australian author as well as a dedicated activist for indigenous sovereignty. In her most recent novel, The Swan Book (2013), Wright contextualises climate change and the extinction anxieties Western urbanized audiences are finding increasingly difficult to ignore within the time frame of the European settlement of Australia, and the much larger time frame of Aboriginal presence on Country. Wright weaves together the memory of the 2007 Emergency Response in the Northern Territory and the perspective of a global climate crisis to provide a narrative that resists both the shortcuts of emergency action and the fascination with end times.